2022
DOI: 10.1007/s11864-022-00962-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Strategies for Colorectal Cancer Screening

Abstract: Opinion statementColorectal cancer (CRC) imposes significant morbidity and mortality, yet it is also largely preventable with evidence-based screening strategies. In May 2021, the US Preventive Services Task Force updated guidance, recommending screening begin at age 45 for average-risk individuals to reduce CRC incidence and mortality in the United States (US). The Task Force recommends screening with one of several screening strategies: high-sensitivity guaiac fecal occult blood test (HSgFOBT), fecal immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 71 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…Colon cancer is one of the cancers with the highest prevalence in the world, its early clinical symptoms are not typical, and most of them are found in the late stage, so the mortality is high. [ 17 ] Although there are no guidelines to determine whether PLA patients should be routinely screened for colon cancer, many scholars believe that PLA is closely associated with colon cancer, especially in patients with Klebsiella pneumoniae infection and diabetes. [ 18 , 19 ] Mohan et al conducted a meta-analysis, which showed that patients with PLA had a much higher incidence of colon cancer than the general population, and over 90% of the pathogenic bacteria were Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is one of the cancers with the highest prevalence in the world, its early clinical symptoms are not typical, and most of them are found in the late stage, so the mortality is high. [ 17 ] Although there are no guidelines to determine whether PLA patients should be routinely screened for colon cancer, many scholars believe that PLA is closely associated with colon cancer, especially in patients with Klebsiella pneumoniae infection and diabetes. [ 18 , 19 ] Mohan et al conducted a meta-analysis, which showed that patients with PLA had a much higher incidence of colon cancer than the general population, and over 90% of the pathogenic bacteria were Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…However, fecal DNA screening is costly, and some uncertainty as to whether further diagnostic tests are necessary when the result is positive but the follow-up colonoscopy is negative. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…CRC screening is more costeffective compared to the absence of screening programs 6 . Based on current scientific research, Fecal Immunochemical Testing (FIT) showed increased participation, has been recommended as the first option for CRC screening, and has a low cost 7 .…”
Section: Introductionmentioning
confidence: 99%